Evolutionary psychology - "Ray, William J" (New Delhi, 2013)
This book brings together current perspectives concerning the manner in which human mind, behavior and experience evolved. In addition to the traditional psychological literature, it draws from work in the cognitive and affective neurosciences, ethology, and genetics. The focus will be on a unification and integration of evolutionary understandings within a broader consideration.
Keywords: Evolutionary psychology